2021
DOI: 10.1210/jendso/bvab141
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemic Emergencies Associated With COVID-19 Vaccination: A Case Series and Discussion

Abstract: Context Hyperglycemic emergencies such as diabetic ketoacidosis (DKA) and hyperosmolar hyperglycemic syndrome (HHS) and new-onset diabetes mellitus (DM) have been reported in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. Hyperglycemia is a predictor of poor prognosis in COVID-19 disease. Objectives The objective of this work is to describe a case series of HHS and/or DKA likely triggered by the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…Abu-Rumaileh et al [ 18 ] reported one patient of HHS, whereas Edwards et al [ 19 ] and Lee et al [ 20 ] each reported three patients of hyperglycemic emergencies respectively. These patients had preexisting or newly diagnosed type 2 diabetes mellitus (T2DM), were older at presentation, had one or more features of metabolic syndrome and one patient had cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abu-Rumaileh et al [ 18 ] reported one patient of HHS, whereas Edwards et al [ 19 ] and Lee et al [ 20 ] each reported three patients of hyperglycemic emergencies respectively. These patients had preexisting or newly diagnosed type 2 diabetes mellitus (T2DM), were older at presentation, had one or more features of metabolic syndrome and one patient had cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, all the patients reported by Abu-Rumaileh et al [ 18 ] and Lee et al [ 20 ] could be transitioned to oral hypoglycemic agents on outpatient follow-up after the initial intravenous fluid and insulin therapy. C-peptide recovery was documented in three patients, further supporting the hypothesis of recovery of β cells and insulinopenia after the acute hyperglycemic emergency.…”
Section: Discussionmentioning
confidence: 99%
“…Several instances of COVID-19 vaccination-induced hyperglycemia (ViHG) and related complications were reported [ 10 , 11 , 12 , 13 ]. Three diabetic individuals (one female and two males) presented with postvaccination hyperglycemia 1–6 days after receiving their first dose of the Covishield (AstraZeneca) vaccine [ 13 ].…”
Section: Vaccine-induced Hyperglycemia (Vihg)—case Reportsmentioning
confidence: 99%
“…Another study reported acute hyperglycemia 20–36 days after administration of the first dose of the Covishield (AstraZeneca) vaccine in three middle-aged obese dyslipidemic male patients (two of whom were prediabetic) [ 11 ]. ViHG was reported after the administration of the mRNA vaccines, Tozinameran/BNT162b2/Comirnaty (Pfizer/BioNTech) and mRNA-1273/Spikevax (Moderna) [ 10 , 12 ]. A summary of their available pre- versus postvaccination metabolic profiles and key data is presented in Table 1 .…”
Section: Vaccine-induced Hyperglycemia (Vihg)—case Reportsmentioning
confidence: 99%
See 1 more Smart Citation